Efficient electricity portfolios for Switzerland and the United States - Boris Krey; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2006)
This study applies financial portfolio theory to determine efficient electricity-generating technology mixes for Switzerland and the United States. Expected returns are given by the (negative of the) rate of increase of power generation cost. Volatility of returns relates to the standard deviation of the cost increase associated with the portfolio, which contains Nuclear, Run of river, Storage hydro and Solar in the case of Switzerland, and Coal, Nuclear, Gas, Oil, and Wind in the case of the United States. Since shocks in generation costs are found to be correlated, the seemingly unrelated regression estimation (SURE) method is applied for filtering out the systematic component of the covariance matrix of the cost changes. Results suggest that at observed generation costs in 2003, the maximum expected return (MER) portfolio for Switzerland would call for a shift towards Nuclear and Solar, and therefore away from Run of river and Storage hydro. By way of contrast, the minimum variance (MV) portfolio mainly contains Nuclear power and Storage hydro. The 2003 MER portfolio for the United States contains Coal generated electricity and Wind, while the MV alternative combines Coal, Nuclear, Oil and Wind. Interestingly, Gas does not play any role in the determination of efficient electricity portfolios in the United States.
Keywords: C32; G11; Q49; 330; energy electricity; portfolio theory; efficiency frontier; seemingly unrelated regression estimations (SURE); Elektrizität; Elektrizitätswirtschaft; Energieversorgung; Portfolio-Management; Schätzung; Schweiz; USA